A nickel-cobalt-manganese-oxide lithium single crystal positive electrode material and a preparation method thereof

By using an airflow crusher and plasma treatment in the preparation process of single crystal positive electrode materials, combined with organic lubricants and fluorine-containing surfactants, the problems of insufficient circulation performance and slow discharge speed of single crystal positive electrode materials are solved, and efficient production and excellent material performance are achieved.

CN116409825BActive Publication Date: 2025-04-04HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310322249.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2025-04-04
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

The circulation performance of single-crystal positive electrode materials is insufficient and the discharge and sieving speeds are slow, which limits its industrial production.

Method used

The single-crystal nickel-cobalt-manganese ternary precursor is mixed with a lithium source and sintered at high temperature. Then, organic lubricant and fluorine-containing surfactant are added to the airflow crusher for gas flow crushing, and plasma treatment is carried out in the fluorine-containing gas to improve the circulation performance and flowability of the material.

Benefits of technology

The circulation performance and discharge efficiency of single crystal positive electrode materials are significantly improved, production time and cost are shortened, and the hydrophobic performance and storage time of the materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116409825B_ABST
    Figure CN116409825B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a single crystal positive electrode material of lithium nickel cobalt manganese oxide, comprising the following steps: S1, mixing a single crystal nickel cobalt manganese ternary precursor with a lithium source, and sintering at high temperature to obtain a sintered material; S2, adding the sintered material, an organic lubricant and a fluorine-containing surfactant to a gas flow mill for gas flow milling to obtain a crushed material; S3, after the crushed material is discharged from the gas flow mill, it is subjected to plasma treatment in a fluorine-containing gas for fluorination, and the crushed material is obtained after sieving. The preparation method of the present invention can effectively improve the cycle performance of the single crystal positive electrode material of lithium nickel cobalt manganese oxide, and greatly shorten the production time, and has the advantages of low energy consumption, safe and reliable production process, low production cost, and easy large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to a nickel cobalt manganese oxide lithium single crystal positive electrode material and a preparation method thereof. Background Art

[0002] As a new type of mobile energy storage device, lithium-ion batteries are expected to be widely used in various energy storage fields, such as static energy storage, smart grids and electric vehicles. Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, separators and electrolytes, among which the performance of positive electrode materials plays a vital role in the performance of lithium-ion batteries. Compared with polycrystalline materials, single-crystal positive electrode materials have excellent thermal stability and mechanical strength. In addition, the charge and discharge performance of single-crystal materials under high voltage is more outstanding. However, the cycle performance of unmodified single-crystal materials is insufficient, so they usually need to be modified to improve their cycle performance before they can be put into use as positive electrode materials. In addition, due to the high hardness of single-crystal materials, it is difficult to crush them, and because more interfaces are exposed during the crushing process, the surface energy of the material increases, so the particles are easy to agglomerate, which increases the difficulty of screening the material. Therefore, the discharge and screening speed of single-crystal materials are slow, resulting in a significant increase in production time and cost, which has become an important limiting factor in the industrial production of single-crystal positive electrode materials. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a single crystal positive electrode material of lithium nickel cobalt manganese oxide and a preparation method thereof.

[0004] The present invention provides a method for preparing a single crystal positive electrode material of lithium nickel cobalt manganese oxide, comprising the following steps:

[0005] S1, mixing a single crystal nickel-cobalt-manganese ternary precursor with a lithium source, and sintering at high temperature to obtain a sintered material;

[0006] S2, adding the sintering material, the organic lubricant and the fluorine-containing surfactant into a jet mill for jet milling to obtain a pulverized material;

[0007] S3, after the crushed material is discharged from the air flow mill, it is subjected to plasma treatment in a fluorine-containing gas for fluorination, and then sieved to obtain the crushed material.

[0008] Preferably, the single crystal nickel-cobalt-manganese ternary precursor is Ni x Co y Mn (1-x-y) (OH)2、Ni x Co y Mn (1-x-y) CO3 or a combination thereof, wherein 0.5≤x≤0.95, 0.02≤y≤0.3; the D50 of the single crystal nickel-cobalt-manganese ternary precursor is 3-6 μm.

[0009] Preferably, the lithium source is at least one of lithium hydroxide, lithium carbonate and lithium acetate.

[0010] Preferably, the ratio of the total amount of metal ion substances in the single crystal nickel-cobalt-manganese precursor to the total amount of lithium substances in the lithium source is 1:0.95-1.15.

[0011] Preferably, in S1, the high temperature sintering step comprises: first sintering at 400-600°C for 4-7h, and then sintering at 780-950°C for 10-25h.

[0012] Preferably, in S2, the air flow crushing pressure is 0.4-0.8 MPa, the classification frequency is 80-130 Hz, and the induced draft fan frequency is 35-60 Hz.

[0013] In the present invention, organic lubricants and fluorine-containing surfactants are compounded and added in appropriate proportions in the air flow pulverization of S2, and the lubrication and grinding aid effects of the organic lubricants and the surface energy reduction effect of the fluorine-containing surfactants can be utilized to achieve a synergistic effect, so that the single crystal material is easy to pulverize, and the particles after pulverization reduce agglomeration and increase fluidity, thereby significantly reducing the time of discharging from the air flow pulverizer. The working principle of the air flow pulverizer is as follows: high-pressure gas is accelerated into a high-speed air flow through a nozzle, and the air flow drives the material particles to accelerate, causing the material to collide, rub, and shear and break. The pulverized material is classified with the air flow to the classification area, and the material that meets the particle size requirements is taken away, and the material that does not meet the particle size requirements returns to the pulverization area to continue pulverization. In this process, the particles will expose a large number of interfaces in a short time after collision, friction, and shearing, and the specific surface energy increases rapidly. In order to reduce the surface energy, agglomerates will be formed between the particles, so the material fluidity deteriorates, and the addition of organic lubricants plays a lubricating role, which can make the particles easier to break and reduce friction. At the same time, the addition of fluorine-containing surfactants can reduce the specific surface energy, reduce particle agglomeration, and improve fluidity. Preferably, the lubricant is at least one of sodium dodecyl sulfate, sodium lauryl sulfate, magnesium lauryl sulfate, triethanolamine, triisopropanolamine, and monoethanol diisopropanolamine. Preferably, the mass ratio of the lubricant to the sintering material is (0.01-1):100; preferably, the fluorine-containing surfactant is at least one of anionic fluorocarbon surfactant, cationic fluorocarbon surfactant, zwitterionic fluorocarbon surfactant, and nonionic fluorocarbon surfactant. Preferably, the mass ratio of the fluorine-containing surfactant to the sintering material is (0.01-1):100.

[0014] Preferably, in S3, the specific steps of fluorination by plasma treatment in fluorine-containing gas include: placing the crushed material in a plasma treatment chamber, first treating it with O2 plasma at a power of 35 to 55 W for 10 to 20 seconds, and then treating it with fluorine-containing gas plasma at a power of 80 to 120 W for 15 to 30 minutes. After the fluorine-containing gas plasma treatment, the surface of the material is modified by F doping, and the bombardment of the surface of the single crystal particles will form F doping, which can improve the cycle performance of the material, so that the cycle performance of the treated single crystal material can meet the use requirements of the positive electrode material. In addition, the organic lubricant on the surface of the single crystal particles is modified by F. - Modification can further improve the hydrophobicity of organic compounds, thereby indirectly improving the hydrophobicity of the bulk material, saving screening time, and saving production time and cost.

[0015] Preferably, the fluorine-containing gas is at least one of C2F6, C3F8, C4F8, C4F6, CHF3, SF6, and NF3.

[0016] A nickel-cobalt-manganese-oxide lithium single crystal positive electrode material is prepared by the preparation method.

[0017] The beneficial effects of the present invention are as follows:

[0018] The present invention can make the single crystal material easier to pulverize by adding an organic lubricant with lubricating and grinding-aiding effects during the airflow pulverization of the single crystal material, thereby obtaining particles with smaller and more uniform particle sizes, which is beneficial to increasing the discharge speed, and can improve the fluidity of the particles after pulverization and reduce agglomeration. At the same time, the addition of a fluorinated surfactant that can reduce the surface energy can reduce the surface energy while increasing the hydrophobicity of the material, making the particles easier to disperse and greatly improving the fluidity of the material. The two can work together to significantly improve the discharge efficiency of the material from the airflow pulverizer, effectively saving production time and cost, and the high hydrophobicity of the material is also beneficial to increasing the storage time of the material.

[0019] The present invention uses fluorine-containing gas plasma to modify the pulverized material discharged from the air flow pulverizer. Since the fluorine-containing gas is ionized at high pressure to generate highly active F - , high-speed particles bombard the surface of single crystal materials, F - Forming chemical bonds with the ions on the surface of the material, F doping is formed by bombarding the surface of the single crystal particles, which can improve the cycle performance of the material, so that the cycle performance of the treated single crystal material can meet the use requirements of the positive electrode material. In addition, bombarding the surface functional groups of the organic lubricant and fluorinated surfactant will further improve the hydrophobicity of the organic matter, thereby indirectly improving the hydrophobicity of the positive electrode material. Therefore, the dispersion performance and fluidity of the finished material are further enhanced, which is conducive to further shortening the screening time, improving production efficiency and reducing costs.

[0020] In summary, the preparation method of the present invention can not only improve the cycle performance of the nickel cobalt manganese oxide lithium single crystal positive electrode material, so that its cycle performance can meet the use requirements of the positive electrode material, but also overcome the problem of slow discharge and screening speed of the single crystal material, greatly shorten the production time of the single crystal positive electrode material, and has the advantages of low energy consumption, safe and reliable production process, low production cost, and easy large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The cycle curves of button batteries of Example 1 and Comparative Examples 3-4 are shown.

[0022] Figure 2 This is a SEM image of the nickel cobalt manganese oxide single crystal positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is described in detail below through specific embodiments.

[0024] Example 1

[0025] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0026] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 890℃ for 12h to obtain the sintered material LiNi 0.7 Co 0.1 Mn 0.2 O2; among them, Ni 0.7 Co 0.1 Mn 0.2 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.04;

[0027] S2, sintering material LiNi 0.7 Co 0.1 Mn 0.2 O2, triethanolamine and 3M fluorocarbon surfactant FC-4430 were added to the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.5MPa, classification frequency was 90Hz, and induced draft fan frequency was 40Hz to obtain pulverized material; triethanolamine and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.3:100, 3M fluorocarbon surfactant FC-4430 and sintering material LiNi 0.7 Co 0.1 Mn 0.2The mass ratio of O2 is 0.5:100;

[0028] S3. After the crushed material is discharged from the air flow mill, it is placed in a plasma treatment chamber, first treated with O2 plasma at a power of 40 W for 15 seconds, and then treated with CF4 plasma at a power of 100 W for 20 minutes, and then sieved to obtain the product.

[0029] Example 2

[0030] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0031] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 890℃ for 12h to obtain the sintered material LiNi 0.7 Co 0.1 Mn 0.2 O2; among them, Ni 0.7 Co 0.1 Mn 0.2 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.04;

[0032] S2, sintering material LiNi 0.7 Co 0.1 Mn 0.2 O2, triethanolamine and 3M fluorocarbon surfactant FC-4430 were added to the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.65MPa, classification frequency was 120Hz, and induced draft fan frequency was 60Hz to obtain pulverized material; triethanolamine and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.3:100, 3M fluorocarbon surfactant FC-4430 and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.5:100;

[0033] S3. After the crushed material is discharged from the air flow mill, it is placed in a plasma treatment chamber, first treated with O2 plasma at a power of 40 W for 15 seconds, and then treated with CF4 plasma at a power of 100 W for 20 minutes, and then sieved to obtain the product.

[0034] Example 3

[0035] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0036] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 890℃ for 12h to obtain the sintered material LiNi 0.7 Co 0.1 Mn 0.2 O2; among them, Ni 0.7 Co 0.1 Mn 0.2 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.04;

[0037] S2, sintering material LiNi 0.7 Co 0.1 Mn 0.2 O2, ethanol diisopropanolamine and 3M fluorocarbon surfactant FC-4430 were added to the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.5MPa, classification frequency was 90Hz, and induced draft fan frequency was 40Hz to obtain pulverized material; wherein ethanol diisopropanolamine and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.5:100, 3M fluorocarbon surfactant FC-4430 and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.5:100;

[0038] S3. After the crushed material is discharged from the air flow mill, it is placed in a plasma treatment chamber, first treated with O2 plasma at a power of 40 W for 15 seconds, and then treated with CF4 plasma at a power of 100 W for 20 minutes, and then sieved to obtain the product.

[0039] Example 4

[0040] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0041] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.5 Co 0.2 Mn 0.3 After (OH)2 and Li2CO3 were mixed, they were sintered at 500℃ for 5h and then at 950℃ for 12h to obtain the sintered material LiNi 0.5 Co 0.2 Mn 0.3 O2; among them, Ni 0.5 Co 0.2 Mn 0.3The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in Li2CO3 is 1:1.06;

[0042] S2, sintering material LiNi 0.5 Co 0.2 Mn 0.3 O2, triethanolamine and 3M fluorocarbon surfactant FC-4430 were added to the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.5MPa, classification frequency was 90Hz, and induced draft fan frequency was 40Hz to obtain pulverized material; triethanolamine and sintering material LiNi 0.5 Co 0.2 Mn 0.3 The mass ratio of O2 is 0.3:100, 3M fluorocarbon surfactant FC-4430 and sintering material LiNi 0.5 Co 0.2 Mn 0.3 The mass ratio of O2 is 0.5:100;

[0043] S3. After the crushed material is discharged from the air flow mill, it is placed in a plasma treatment chamber, first treated with O2 plasma at a power of 40 W for 15 seconds, and then treated with CF4 plasma at a power of 100 W for 20 minutes, and then sieved to obtain the product.

[0044] Example 5

[0045] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0046] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.95 Co 0.02 Mn 0.03 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 780℃ for 12h to obtain the sintered material LiNi 0.95 Co 0.02 Mn 0.03 O2; among them, Ni 0.95 Co 0.02 Mn 0.03 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.01;

[0047] S2, sintering material LiNi 0.95 Co 0.02 Mn 0.03 O2, triethanolamine and Chemours FS-3100 fluorocarbon surfactant were added to the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.5MPa, classification frequency was 90Hz, and induced draft fan frequency was 40Hz to obtain pulverized material; triethanolamine and sintering material LiNi 0.95Co 0.02 Mn 0.03 The mass ratio of O2 is 0.3:100, Chemours FS-3100 fluorocarbon surfactant and sintering material LiNi 0.95 Co 0.02 Mn 0.03 The mass ratio of O2 is 0.5:100;

[0048] S3. After the crushed material is discharged from the air flow mill, it is placed in a plasma treatment chamber, first treated with O2 plasma at a power of 40 W for 15 seconds, and then treated with CF4 plasma at a power of 100 W for 20 minutes, and then sieved to obtain the product.

[0049] Comparative Example 1

[0050] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0051] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 890℃ for 12h to obtain the sintered material LiNi 0.7 Co 0.1 Mn 0.2 O2; among them, Ni 0.7 Co 0.1 Mn 0.2 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.04;

[0052] S2, sintering material LiNi 0.7 Co 0.1 Mn 0.2 O2 and 3M fluorocarbon surfactant FC-4430 were added to the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.5MPa, classification frequency was 90Hz, and induced draft fan frequency was 40Hz to obtain pulverized material; 3M fluorocarbon surfactant FC-4430 and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.8:100;

[0053] S3. After the crushed material is discharged from the air flow mill, it is placed in a plasma treatment chamber, first treated with O2 plasma at a power of 40 W for 15 seconds, and then treated with CF4 plasma at a power of 100 W for 20 minutes, and then sieved to obtain the product.

[0054] Comparative Example 2

[0055] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0056] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 890℃ for 12h to obtain the sintered material LiNi 0.7 Co 0.1 Mn 0.2 O2; among them, Ni 0.7 Co 0.1 Mn 0.2 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.04;

[0057] S2, sintering material LiNi 0.7 Co 0.1 Mn 0.2 O2 and triethanolamine were added into the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.5MPa, classification frequency was 90Hz, and induced draft fan frequency was 40Hz to obtain pulverized material; triethanolamine and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.8:100;

[0058] S3. After the crushed material is discharged from the air flow mill, it is placed in a plasma treatment chamber, first treated with O2 plasma at a power of 40 W for 15 seconds, and then treated with CF4 plasma at a power of 100 W for 20 minutes, and then sieved to obtain the product.

[0059] Comparative Example 3

[0060] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0061] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 890℃ for 12h to obtain the sintered material LiNi 0.7 Co 0.1 Mn 0.2 O2; among them, Ni 0.7 Co 0.1 Mn 0.2 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.04;

[0062] S2, sintering material LiNi 0.7 Co0.1 Mn 0.2 O2, triethanolamine and 3M fluorocarbon surfactant FC-4430 were added to the air flow mill for air flow pulverization. The air flow pulverization parameters were controlled as follows: pulverization pressure was 0.5MPa, classification frequency was 90Hz, and induced draft fan frequency was 40Hz. The pulverized material was obtained after sieving. Among them, triethanolamine and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.3:100, 3M fluorocarbon surfactant FC-4430 and sintering material LiNi 0.7 Co 0.1 Mn 0.2 The mass ratio of O2 is 0.5:100.

[0063] Comparative Example 4

[0064] Preparation of lithium nickel cobalt manganese oxide single crystal positive electrode material:

[0065] S1, the single crystal nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 After (OH)2 and LiOH·H2O were mixed, they were sintered at 500℃ for 5h and then at 890℃ for 12h to obtain the sintered material LiNi 0.7 Co 0.1 Mn 0.2 O2; among them, Ni 0.7 Co 0.1 Mn 0.2 The ratio of the total amount of metal ion substances in (OH)2 to the total amount of lithium substances in LiOH·H2O is 1:1.04;

[0066] S2, sintering material LiNi 0.7 Co 0.1 Mn 0.2 O2 is added into the air flow mill for air flow pulverization. The air flow pulverization parameters are controlled as follows: pulverization pressure is 0.5 MPa, classification frequency is 90 Hz, and induced draft fan frequency is 40 Hz. The pulverized material is obtained after sieving.

[0067] Test example

[0068] In addition, the finished materials of Example 1 and Comparative Examples 3-4 are used as positive electrode active materials, lithium sheets as negative electrodes, superconducting carbon black Super P as conductive agents, polyvinylidene fluoride (PVDF) as binders, and N-methylpyrrolidone (NMP) as solvents. The positive electrode active material and superconducting carbon black Super P are ground and then added to a solution of N-methylpyrrolidone dissolved with polyvinylidene fluoride. The mass ratio of the positive electrode active material, Super P and PVDF is 8:1:1. After stirring for 2 hours, the mixture is coated on the surface of a 20 μm thick aluminum foil and then vacuum dried at 110 ° C for 20 hours. The dried pole piece is rolled, sliced, and weighed, and then assembled into a CR2016 button battery with a metal lithium sheet and a diaphragm prepared by a wet process in an argon atmosphere glove box. The electrolyte is 1.0 mol / L LiPF6 / EC+DEC+EMC. The assembled button cell was tested for electrochemical performance. First, the button cell was activated, and then cycled at a voltage range of 2.8-4.35V and a rate of 1C. Figure 1 It is the cycle curve diagram of button-type batteries of Example 1 and Comparative Examples 3-4.

[0069] according to Figure 1 It can be seen from the cycle data of Example 1 and Comparative Examples 3-4 that Example 1 has the best cycle performance, with a 50-week capacity retention rate of 98.2%. Comparative Example 4 has the worst cycle performance without any surface treatment, but Comparative Example 3 has been treated with an organic lubricant and a fluorinated surfactant but not fluorinated, and its cycle performance is between that of Example 1 and Comparative Example 4. This is because the treatment with an organic lubricant and a fluorinated surfactant can reduce agglomeration and reduce the content of fine powder, thereby improving the cycle performance of the material to a certain extent. However, due to the lack of fluorination treatment, the cycle performance is still far behind that of the material in Example 1. It can be seen from the above data that the cycle performance of the single crystal material that has not been fluorinated is poor, and the present invention can significantly improve the cycle performance of the single crystal material by fluorinating the single crystal material, so that it can meet the use requirements of the positive electrode material.

[0070] The sample prepared in Example 1 was characterized by SEM, and the obtained SEM image is as follows Figure 2 The samples prepared in Example 1 and Comparative Examples 1-4 were tested for particle size, and the feeding rates of the crushed materials obtained by S2 in Example 1 and Comparative Examples 1-4, as well as the screening rates of the single crystal positive electrode materials finally obtained in Example 1 and Comparative Examples 1-4 were respectively counted, with the mesh number of the sieve being 150 meshes, and the data are shown in Table 1.

[0071] Table 1 Particle size, feeding rate, and sieving rate data of samples prepared in Example 1 and Comparative Examples 1-4

[0072]

[0073]

[0074] According to the data in Table 1, for samples sintered under the same conditions and crushed under the same conditions, the particle size of Example 1 is smaller and more in line with the index requirements. The material feeding rate is significantly improved under the dual effects of lubricant and fluorinated surfactant, which can greatly improve production efficiency and reduce costs. Figure 1 The SEM images in the figure show that the single crystal particles are in a good broken state, with almost no particle damage or agglomeration. The final finished product material was screened and it was also confirmed that the addition of organic lubricants and fluorinated surfactants can improve the screening performance. This is because the addition of organic lubricants can make the material more fully broken, forming particles with better and more uniform particle sizes, and the addition of organic lubricants and fluorinated surfactants can also improve the fluidity of the material. The improved fluidity leads to improved screening performance, which further improves production efficiency in the screening stage. Therefore, the entire production process time is greatly shortened, effectively reducing costs. The data of Example 1 are compared with those of Comparative Examples 1-4. In Comparative Example 1, no organic lubricant is added during airflow pulverization. The results show that the particle size of the particles is relatively large, indicating that the crushing is not sufficient, resulting in a slow feed rate and screening rate. In Comparative Example 2, no fluorinated surfactant is added during airflow pulverization. The surface energy of the material is relatively large during pulverization, agglomeration occurs, and the dispersibility and fluidity are low, resulting in a slow feed rate and screening rate. In Comparative Example 3, no fluorination treatment is performed after airflow pulverization. The fluidity and dispersibility are not as good as those of the fluorinated material in Example 1, and the screening rate is reduced. Comparative Example 4 does not perform any special treatment. It can be seen that the material feed rate and screening rate are very slow, which seriously affects the production efficiency.

[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a single crystal positive electrode material of lithium nickel cobalt manganese oxide, characterized in that: The following steps are involved: S1, mixing a single crystal nickel-cobalt-manganese ternary precursor with a lithium source, and sintering at high temperature to obtain a sintered material; S2, adding the sintering material, the organic lubricant and the fluorine-containing surfactant into a jet mill for jet milling to obtain a pulverized material; S3, after the crushed material is discharged from the air flow mill, it is subjected to plasma treatment in a fluorine-containing gas for fluorination, and then sieved to obtain the crushed material.

2. The method for preparing the nickel cobalt lithium manganese oxide single crystal positive electrode material according to claim 1, characterized in that: The single crystal nickel-cobalt-manganese ternary precursor is Ni x Co y Mn (1-x-y) (OH)2、Ni x Co y Mn (1-x-y) CO3 or a combination thereof, wherein 0.5≤x≤0.95, 0.02≤y≤0.3; the D50 of the single crystal nickel-cobalt-manganese ternary precursor is 3-6 μm; The lithium source is at least one of lithium hydroxide, lithium carbonate and lithium acetate; The ratio of the total amount of metal ion substances in the single crystal nickel-cobalt-manganese ternary precursor to the total amount of lithium substances in the lithium source is 1:0.95-1.

15.

3. The method for preparing the nickel cobalt lithium manganese oxide single crystal positive electrode material according to claim 1, characterized in that: In S1, the high temperature sintering step includes: first sintering at 400-600°C for 4-7h, and then sintering at 780-950°C for 10-25h.

4. The method for preparing the nickel cobalt lithium manganese oxide single crystal positive electrode material according to claim 1, characterized in that: In S2, the pressure of the air flow crushing is 0.4-0.8 MPa, the classification frequency is 80-130 Hz, and the frequency of the induced draft fan is 35-60 Hz.

5. The method for preparing the nickel-cobalt-lithium-manganese oxide single crystal positive electrode material according to claim 1, characterized in that: The organic lubricant is at least one of sodium dodecyl sulfate, sodium lauryl sulfate, magnesium lauryl sulfate, triethanolamine, triisopropanolamine, and monoethanoldiisopropanolamine; the fluorine-containing surfactant is at least one of anionic fluorocarbon surfactants, cationic fluorocarbon surfactants, zwitterionic fluorocarbon surfactants, and nonionic fluorocarbon surfactants.

6. The method for preparing the nickel cobalt lithium manganese oxide single crystal positive electrode material according to claim 1, characterized in that: The mass ratio of the organic lubricant to the sintering material is (0.01-1):100, and the mass ratio of the fluorine-containing surfactant to the sintering material is (0.01-1):

100.

7. The method for preparing a single crystal positive electrode material of nickel cobalt lithium manganese oxide according to claim 1, characterized in that: In S3, the specific steps of subjecting the crushed material to plasma treatment in a fluorine-containing gas for fluorination include: placing the crushed material in a plasma treatment chamber, first treating it with O2 plasma at a power of 35 to 55 W for 10 to 20 seconds, and then treating it with fluorine-containing gas plasma at a power of 80 to 120 W for 15 to 30 minutes.

8. The method for preparing a single crystal positive electrode material of nickel cobalt lithium manganese oxide according to claim 1, characterized in that: In S3, the fluorine-containing gas is at least one of C2F6, C3F8, C4F8, C4F6, CHF3, SF6, and NF3.

9. A single crystal positive electrode material of lithium nickel cobalt manganese oxide, characterized in that: The method is prepared according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Single crystal high-capacity nickel-cobalt lithium manganate positive electrode material and preparation method thereof

    CN110061225A

  • Single crystal lithium ion battery ternary electrode material precursor, electrode material, and preparation method and application thereof

    CN110444757A